Mercury supramolecular architectures constructed from flexible unsymmetrical bis(pyridyl) ligands: Structural motif mediated by mercury-halide clusters, ligand conformations and non-covalent interactions. (15th October 2016) - Ye, Zheng-Yang; Zhang, Zhu-Yan; Huo, Li-Hua; Deng, Zhao-Peng; Zhang, Xian-Fa; Gao, Shan
Graphical abstract: The solvent reaction of five flexible unsymmetrical bis(pyridyl) ligands with HgX2 (X = Cl −, Br − and I − ) salts leads to the formation of fifteen Hg(II) complexes. The different N1s binding energies can be attributed to N atoms with different chemical environments. Abstract: The solvent reaction of five flexible unsymmetrical bis(pyridyl) ligands, N -(pyridin-2-ylmethyl)pyridin-2-amine (L1 ), N -(pyridin-2-ylmethyl)pyridin-3-amine (L2 ), N -(pyridin-3-ylmethyl)pyridin-2-amine (L3 ), N -(pyridin-3-ylmethyl)pyridin-3-amine (L4 ) and N -(pyridin-4-ylmethyl)pyridin-3-amine (L5 ), with HgX2 (X = Cl −, Br − and I − ) salts leads to the formation of fifteen Hg(II) complexes, namely [Hg(L1 )X2 ] n [X = Cl (1 ) and Br (2 )], [Hg2 I6 ] 2− ·2HL1 + (3 ), [Hg(L2 )Cl2 ]2 (4 ), [Hg(L2 )X2 ] n [X = Br (5 ) and I (6 )], [Hg(L3 )Cl2 ] n (7 ), [Hg(HL3 )X3 ] [X = Br (8 ) and I (9 )], [Hg(L4 )Cl2 ] n (10 ), [HgX4 ] 2− ·2HL4 + [X = Br (11 ) and I (12 )], [Hg3 Cl10 ] 4− ·2H2 L5 2+ (13 ) and [Hg2 (L5 )(HL5 )X5 ] [X = Br (14 ) and I (15 )], which have been characterized by elemental analysis, IR, TG, PL, XPS, powder and single-crystal X-ray diffraction. Structural analyses indicate that complexes1, 2, 5 –7 and10 exhibit linear or helical chain motifs while complex4 shows a [2+2] metallomacrocyclic structure. Complexes8, 9, 14 and15 present simple mono- or dinuclear motifs, in which the Hg(II) cations exist in HgNX3 or Hg2 N2 X5 (X = Br and I) spheres. On the contrary, under the same conditions, complexes3 and11–13 are obtained as ionic salts composed of protonated bis(pyridyl) ligands and various mercury-halide clusters, [HgX4 ] 2− (X = Br − and I − ), [Hg2 I6 ] 2− or [Hg3 Cl10 ] 4− . The structural diversities and evolutions of these architectures can be attributed to the diverse mercury-halide clusters, the ligand conformation ( cis – trans, trans – cis, trans – trans ) as well as non-covalent interactions, such as C/N–H⋯X, C–H⋯π, π⋯π and Cl⋯π. Moreover, the binding energies of the Hg 4f7/2 level in the XPS spectra present a regular decrease from Cl-containing, Br-containing to I-containing complexes. For the N1s core level, the different binding energies in the XPS spectra can be attributed to the N atoms with different chemical environments.